Upaya Meningkatkan Pemahaman Siswa Kelas 10 Tentang Materi Sig Melalui Project Based Learning pada Mata Pelajaran Geografi di SMAN 1 Galang - Angelina Sipayung; Nurmala Berutu (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
Education has a very important role in forming a generation that is intelligent, creative and has the ability to think critically. This research aims to improve the learning understanding of class 10 students at SMA Negeri 1 Galang on GIS material through a Project Based Learning (PBL) learning model. This research can provide new insights into the use of the Project Based Learning approach as an effective learning method in teaching complex material. This research uses the Kemmis and Mc model. Taggart as a PTK procedure, which consists of two cycles. Each cycle consists of implementation, action, observation and reflection. From this research, it was found that the Project-Based Learning (PBL) learning model can improve the understanding of class 10 students at SMAN 1 Galang in Geographic Information Systems (GIS) material in geography subjects. This increase in understanding can be seen from the increase in the average value in the cycle -1 and cycle-2 application of the Project-Based Learning (PBL) model. The average value of students in cycle-1 was 81.94 and in cycle-2 there was an increase in the average value of students by 91.94. The implementation of the Project-Based Learning (PBL) model is considered successful in increasing students' understanding because they have achieved the predetermined success indicators.